Building a Dynamic Pricing Engine with Machine Learning for Retail - Akhilesh Kota, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This technical article presents a comprehensive analysis of a machine learning-based dynamic pricing engine designed for retail environments. The system leverages advanced microservices architecture, real-time data processing, and sophisticated machine-learning algorithms to optimize pricing decisions across diverse market conditions. We explore the implementation of a scalable solution that combines high-frequency data processing with intelligent price optimization, incorporating competitive analysis, demand patterns, and inventory management. The architecture employs distributed computing principles, featuring robust data ingestion, advanced feature processing, and multi-model machine learning components. Our findings demonstrate significant improvements in revenue optimization, operational efficiency, and market competitiveness while maintaining high system reliability and security standards.
Keywords: Machine Learning; Dynamic Pricing; Real-time Processing; Microservices Architecture; Retail Optimization